2018
DOI: 10.1002/acr.23442
|View full text |Cite
|
Sign up to set email alerts
|

Does Education Level Mitigate the Effect of Poverty on Total Knee Arthroplasty Outcomes?

Abstract: In poor communities, those without college attain 2-year WOMAC scores that are 10 points worse than those with some college; education has no impact on TKA outcomes in wealthy communities. How education protects those in impoverished communities warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
2
21
1
1
Order By: Relevance
“…Of the status markers, neither objective nor subjective social status indices during childhood or present day significantly related to temporal summation across groups. This finding differs from prior work describing significant relationships between social status and physical pain 8 , 28 , 30 , 32 , 40 , 44 , 48 , 57 , 62 , 66 , 81 , 87 and temporal summation. 38 Instead, downward changes in objective (ie, family household income decreased over time) and subjective social status (ie, subjective social status decreased over time) across the lifespan—such that individuals reported a decrease in status since childhood—significantly correlated with greater temporal summation for Latinx-Americans.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of the status markers, neither objective nor subjective social status indices during childhood or present day significantly related to temporal summation across groups. This finding differs from prior work describing significant relationships between social status and physical pain 8 , 28 , 30 , 32 , 40 , 44 , 48 , 57 , 62 , 66 , 81 , 87 and temporal summation. 38 Instead, downward changes in objective (ie, family household income decreased over time) and subjective social status (ie, subjective social status decreased over time) across the lifespan—such that individuals reported a decrease in status since childhood—significantly correlated with greater temporal summation for Latinx-Americans.…”
Section: Discussioncontrasting
confidence: 99%
“…Low social status relates to poorer physical health, 1 , 2 , 21 , 94 including for Latinx-Americans. 34 , 36 , 73 For pain, objective 8 , 28 , 30 , 32 , 40 , 44 , 48 , 57 , 62 , 81 and subjective social status markers 87 relate with greater chronic pain rates and severity, along with worse pain outcomes. 8 , 28 , 30 , 44 , 57 , 62 , 81 Poverty status likewise inversely correlates with temporal summation among middle-to-older aged adults with knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…While minority status was not found to be a significant predictor of any RA disease outcomes, this may be due to the characteristics of the present cohort. The cohort consisted of majority White females with some college education or higher, and we have previously demonstrated that education can mitigate the effects of poverty on arthroplasty outcomes, but in this study, both white and minority patients had similar education, limiting the potential for introducing bias [2]. As most patients receive care in community hospitals where a broader range of education and individual level income exists our results may not be generalizable.…”
Section: Discussionmentioning
confidence: 73%
“…Interactions between social factors may be complex. For instance, race and poverty are associated with worse arthroplasty outcomes, but education may mitigate the effect of poverty within poor communities [2]. In addition, worse arthroplasty outcomes associated with Black race are not seen for Black patients residing in communities with less than 10% poverty [3].…”
Section: Introductionmentioning
confidence: 99%
“…Blacks are at increased risk of total knee replacement (TKR) revision compared to whites , and blacks report significantly more pain and worse function 2 years after TKR . We previously showed that racial disparities in patient‐reported outcomes are strongly influenced by community poverty and education . Whether disparities in TKR revision risk are related to poverty is unknown.…”
Section: Introductionmentioning
confidence: 99%